PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF IMMUNITY AGAINST HARMFUL HABITS IN FUTURE TEACHERS (Web of Technology: Multidimensional Research Journal, 2025)
In this article, students’ daily activities, students' routines and the culture of using mobile devices, prevention of harmful habits in students, ways to get rid of stress, and meaningful organization of students' free time are described in this article.